2018
DOI: 10.1108/bfj-01-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy knowledge, attitudes, and resources of restaurant employees

Abstract: Purpose Restaurants are unique and challenging environments for accommodating food allergies. The purpose of this paper is to evaluate food allergy knowledge, attitudes and resources among restaurant employees, and identify differences based on restaurant mode of operation. Design/methodology/approach A total of 209 food-service workers were surveyed in full-service restaurants across Southern Ontario, Canada. A paper-based questionnaire was used to evaluate participants’ food allergy knowledge, attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…This loss of control and the need to rely on others highlights the quandaries parents face in social situations when going on holidays, eating out at restaurants, and/or leaving their child in the care of others. 6 , 10 , 19 However, when parents are shunned, labelled a ”helicopter parent” or worse still, not believed, this creates a heightened sense of anxiety and fear and can significantly impact QoL, increase social isolation, and lead to feelings of guilt. 6 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This loss of control and the need to rely on others highlights the quandaries parents face in social situations when going on holidays, eating out at restaurants, and/or leaving their child in the care of others. 6 , 10 , 19 However, when parents are shunned, labelled a ”helicopter parent” or worse still, not believed, this creates a heightened sense of anxiety and fear and can significantly impact QoL, increase social isolation, and lead to feelings of guilt. 6 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…As studies show allergic reactions occur more frequently outside the home, there is a need for specialised training and greater awareness of food allergies in the hospitality and food industries. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Most staff feel it offers little value, perhaps because it does not take into account an individual's particular learning style and this suggests that there is little engagement with the training provided. A failure to fully understand what allergens are, which echoes the findings of Bailey et al [14] and how they can contaminate food, therefore puts allergen sufferers at risk due to inappropriate practices.…”
Section: Discussionmentioning
confidence: 98%
“…McAdams et al [14] found that chefs were knowledgeable about food allergies and were passionate about providing safe meals to guests. However, the same study concluded that there was a general lack of access to important food allergen risk management resources and training.…”
mentioning
confidence: 99%
See 1 more Smart Citation